FAKTOR FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN MASYARAKAT YOGYAKARTA PADA APLIKASI SHOPEE (Prosiding dan Call Paper Widya Wiwaha, 2023)
86% of Indonesian internet users shop online. Therefore online shopping is one of the choices of consumers to meet their needs. The existence of the Shopee application makes it easier for consumers to shop, more practical and economical in transportation costs so that consumers are more comfortable shopping than shopping directly at the store. This makes separate considerations by consumers. In this study we try to find out the factors that influence the purchasing decision of the Yogyakarta community when using the Shopee application. This study aims to: (1) analyze the quality of service and price that affect purchases on shopee users. (2) analyzing prices that influence purchases on shopee users. The population in this study were Yogyakarta residents who used the Shopee application to shop online. The sample for this study was determined using a purposive sampling technique of 49 people. This research is included in the type of qualitative research. The results of this study indicate that based on the results of the research and discussion of what factors influence the purchasing decisions of the Yogyakarta community on the shopee application, the results are: (1) price can indicate the brand quality of a product where consumers have the notion that high prices have good quality . (2) Good service quality will encourage consumers to become repeat buyers. (3) price and service quality affect the purchasing decision of the people of Yogyakarta in considering purchases on the shopee application
Keywords: price; service quality; purchase decision